Synchronization of Optomechanical Oscillators in Coupled 1D Optomechanical Crystal Nanobeam Cavities - Yang Liu; Fei Gao; Daquan Yang; Aiqiang Wang; Mengchen Zhou; Shanchuang Li; Lu Gao; Ze Zhang (Photonics, 2022)
We proposed a new optomechanical system (OMS) based on parallel suspended one-dimensional optomechanical crystal (1D-OMC) nanobeam cavities for optomechanical synchronization. The optomechanical oscillators (OMOs) were spaced apart by an air-slot gap and coupled through optical radiation fields. The numerical simulation showed that the evolution process of 1D-OMC nanobeam cavities to mechanical synchronization could be divided into three clear stages. The synchronization of two mechanical breathing modes at 5.8846 GHz was achieved by using a single laser source. Finally, we investigated the relationship between the threshold power and detuning of an input laser for self-sustaining and synchronization states. Such chip-based structures hold great potential for large-scale synchronized oscillator networks.